Transformation of Vegetable Cultivation Systems Through Vertical Farming on Dry Land in the Niufmolo Farmers Group, East Nusa Tenggara: Transformasi Sistem Budidaya Sayuran Melalui Vertikultur di Lahan Kering pada Kelompok Tani Niufmolo, Nusa Tenggara Timur - Tobing, Wilda Lumban; Sipayung, Boanerges Putra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Niufmolo is a farmer group located in Niufmolo Village with dry land biophysics with a dry climate that results in low productivity and partner income. Its management requires innovation and technology to be used as agricultural land. Verticulture as a transformation of vegetable cultivation is adopted to overcome several problems in farmer groups. This program aims to increase the productivity and income of the Niufmolo farmer group through verticulture technology on dry land. The method of implementing activities is through direct counseling and training. The results show an increase in pak choy productivity of 220-225 kg and income of IDR 5,000,000 in one planting cycle, an increase of 100% compared to conventional methods. This technology is a model for agricultural sustainability in dry climate areas